Recent advances in electrocatalysts for seawater splitting - Guangbo Liu; Yingshuang Xu; Teng Yang; Luhua Jiang (Nano Materials Science, 2023)
Water splitting is an effective strategy to produce renewable and sustainable hydrogen energy. Especially, seawater splitting, avoiding use of the limited freshwater resource, is more intriguing. Nowadays, electrocatalysts explored for hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) using natural seawater or saline electrolyte have been increasingly reported. To better understand the current status and challenges of the electrocatalysts for HER and OER from seawater, we comprehensively review the recent advances in electrocatalysts for seawater splitting. The fundamentals, challenges and possible strategies for seawater splitting are firstly presented. Then, the recently reported electrocatalysts that explored for HER and OER from seawater are summarized and discussed. Finally, the perspectives in the development of high-efficient electrocatalysts for seawater splitting are also proposed.